HUBUNGAN KETERAMPILAN POLA ASUH HOLISTIK DENGAN PERKEMBANGAN ANAK - Tri Sunarsih,; Astuti, Endah Puji; Shanti, Elvika Fit Ari (Jurnal Kesehatan, 2024)
The first five years is a very short period and cannot be repeated, so it is often called the "golden period". Children are the next generation of the nation who deserve attention. Every child has the right to achieve optimal development. Developmental disorders usually occur in childhood affecting multiple functional domains and often persist into adulthood. Parental skills are an effective intervention for child development outcomes. Holistic parenting skills are comprehensive parenting skills that mothers give to their children. Objective: To see holistic parenting skills with child development. Research method: This type of research uses quantitative research. The design in this study is to use an analytical survey design with a cross-sectional approach. The population in this study were all toddlers < 60 months in Ngalang Village, Gedangsari Health Center, Gunungkidul Regency in 2020 with a total of 366 samples, the sampling technique used total sampling. Data analysis using Chi-Square Test. Results: There is no significant relationship between nutritional skills and child development skills with a P value (0.237) > (0.05) and there is a significant relationship between parenting skills and child development with a P value (0.023) < (0 ,05). Conclusion: There is no significant relationship between nutritional fulfillment skills and child development and there is a significant relationship between child care skills and child development.